Characterization and classification of shallow, medium deep and deep red and black soils of northern Telangana zone in Andhra Pradesh - Satyavathi, P.L.A.; Reddy, M. Suryanarayan (Journal of Tropical Agriculture, 2006)
Six pedons representing shallow, medium deep and deep red and black soils of Northern Telangana region under hot, moist, semiarid eco-subregion in Andhra Pradesh were studied morphologically and soil samples were analyzed for physical and chemical properties using standard methods. There is wide variation in colour, structure, texture, reaction and in other physical and chemical properties of the soils between these two broad groups of soils. All red soil pedons were noncalcareous, whereas black soils were calcareous. Cracks and slickensides were the characteristic features of black soils whereas significant increase in clay content in deeper horizons and occurrence of clay films were the characteristic features in red soils. Red soils were classified as Typic Ustipsamments and Typic Haplustalfs. The black soils were classified as Vertic Calciustepts, Vertic Haplustepts and Typic Haplusterts at subgroup level. At the family level, the soils were qualified from sandy to clayey particle size classes, mixed and smectitic mineralogy class and isohyperthermic soil temperature class.